Bolivia : Ex-Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents key findings of the Ex Post Assessment of Longer-Term Program Engagement for Bolivia. Bolivia is a country that is perceived as having one of the best structural reform records in Latin America but experienced sluggish per capita growth, and made virtually no progress in reducing income-based poverty measures. The paper presents a summary account of Bolivia's performance under IMF-supported programs. It emphasizes that to address Bolivia's main economic problems-insufficient growth, and fiscal and financial fragility-a new medium-term program should be focused on fundamental institutional and structural reforms.